PENGARUH SENAM HAMIL TERHADAP PENURUNAN NYERI PUNGGUNG PADA IBU HAMIL TRIMESTER KETIGA DI PUSKESMAS BANGKALAN - Merlyna Suryaningsih (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2019)
Pregnancy causes most of the woman's body to change and will cause the emergence of one of the back pain complaints. Based on preliminary study of 8 (80%) of 10 third trimester pregnant women complained impaired in doing activity while the rest did not complain disturbed in doing its activity. The purpose of this study to analyze the influence of pregnancy exercise to decrease back pain in third trimester pregnant women at health center bangkalan. This research uses Quasy Experimental design with pretest-posttes with control groub approach. Independent variable is pregnancy exercise, dependent variable is decrease of back pain in pregnant mother of trimester III. The population was third trimester pregnant women at Bangkalan Health Center and the sample were 18 people, 9 treatment groups, and 9 control groups using purposive sampling technique. The result of this research is paired t test and independent test with α: 0,05 The results showed that the pre and post treatment group in the analysis using paired t test in get P value: 0.000 <α: 0,05, This shows that H0 is rejected that there is difference of pre and post pain level of treatment group. While in the control group in the analysis using paired t test in get P value: 0.001 <α 0.05 this means H0 rejected, then there are differences in pre and post pain level of control group. And the results were analyzed using independent t-test in both groups obtained P Value: 0.000 <α: 0,05, it shows that H0 is rejected, hence there is difference of pain scale scale between treatment group and control group. It is expected that health workers to improve services and more intensive both quality and quantity in providing counseling to pregnant women about the benefits of pregnancy exercise to prevent back pain complaints